LEGITIMATION OF AGGRESSION AGAINST UKRAINE IN RUSSIAN OFFICIAL DISCOURSE - Demian Shevko (Стратегічна панорама, 2020)
The article examines some aspects of the political legitimization of illegal actions in international relations through the Kremlin's official discourse aiming to justify aggression against Ukraine. To "normalize" its actions in the international arena, Russian authorities organize large-scale and well-coordinated information campaigns, which, combined with diplomatic and economic pressure and other non-military measures, threaten to destabilize the global security. Enjoying virtually total control over the media within Russia and a using a number of powerful international media tools, Russia's political elites are trying to create an alternative political discursive reality to convince different target audiences of the "rationality" of their actions and influence their behavior accordingly. These measures constitute an integral part of Moscow's official discoursewith main goal to restore Soviet era geopolitical power and achieve strategic balance in the civilizational confrontation with the West. The article provides a brief theoretical analysis of the concepts of "legitimacy" and "discourse" in the context of international relations and causalities between Russia’s attempts to legitimize aggression against Ukraine and the Kremlin's perceptions of identity, historical memory and foreign policy. Based on the analysis of the existing scientific literature in the field of legitimation of political actions in the international arena, following categorization of legitimation strategies used by the Russian Federation in official discourse to justify annexation of Crimea and armed aggression in Donbass is proposed: 1) legitimation through reference to customs, laws and traditions; 2) legitimation by appealing to altruism and a certain system of moral and humanitarian values; 3) legitimation through rationalization, theorizing; 4) legitimation through emotions and a hypothetical future. The use of Kremlin discursive practices and legitimation strategies is illustrated by analyzing the text and talk of Vladimir Putin and other leaders of Russian political elite.